Compatibility of Functionalized Graphene with Polyethylene and Its Copolymers. (27th October 2013) - Seo, Hyeon Myeong; Park, Jin Ho; Dao, Trung Dung; Jeong, Han Mo
Abstract : The compatibility of polyethylene (PE) with a functionalized graphene sheet (FGS), which was prepared by the thermal reduction of graphite oxide, was examined in this study. The dispersion of the FGS in the PE was improved as the molecular weight of the PE was decreased. The PE copolymers containing polar comonomers such as maleic anhydride or acrylic acid exhibited better compatibility with FGS than the PE homopolymers. The compatibility of the FGS with PE copolymers containing small amounts of comonomers, which have a solubility parameter slightly larger [up to approximately 0.5 (J/cm 3 ) 1/2 ] than that of PE itself, was better than the compatibility of both the PE and PE copolymers containing larger amounts of comonomers. The morphology, electric conductivity, and tensile properties of FGS/PE copolymer/PE nanocomposites showed that the copolymers with a solubility parameter slightly larger than that of PE effectively served as a compatibilizer in FGS/PE nanocomposites.